An analysis lexical cohesion on Ellen Show with Michelle Obama - Krisna, Natalia; Mubarak, Zia Hisni (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This study applied a discourse analysis study to obtain the types of Lexical Cohesion in YouTube